2009
DOI: 10.1007/s00247-009-1213-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings in 512 children following all-terrain vehicle injuries

Abstract: Head and extremity injuries are the two most common injuries in children suffering ATV injuries and are associated with long-term disability. ATV use by children is dangerous and is a significant threat to child safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In fact, head and extremity injuries are the 2 most common injuries in pediatric patients with ATV-related injuries; many of those injuries are associated with long-term disability. 12 Only 21 states mandate helmet use for ATV riders. However, compliance with such laws is low.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, head and extremity injuries are the 2 most common injuries in pediatric patients with ATV-related injuries; many of those injuries are associated with long-term disability. 12 Only 21 states mandate helmet use for ATV riders. However, compliance with such laws is low.…”
Section: Discussionmentioning
confidence: 99%
“…127 In a series of 73 children presenting to a pediatric trauma center after an ATV accident, nearly half of the patients had extremity fractures, 8 of which were open fractures. 115 At a Canadian tertiary-care pediatric facility, ATV-related fractures and/or dislocations were 1.5 times more common than bicycle-related fractures. 115 At a Canadian tertiary-care pediatric facility, ATV-related fractures and/or dislocations were 1.5 times more common than bicycle-related fractures.…”
Section: All-terrain Vehiclesmentioning
confidence: 98%
“…9 Of long bone injuries, femoral fractures are the most frequently reported followed hip dislocations, tibial-fibular fractures and partial foot amputations. 15 Upper limb fractures are less common. 18 Although rarely reported, 9 vertebral fractures (as illustrated by Case 1 in the present series) cause significant morbidity and in the case of cervical fractures they are often incompatible with life.…”
Section: Musculoskeletal/orthopaedic Injurymentioning
confidence: 99%
“…5,15 It has been reported that loss of consciousness occurs in over half of ATV related injuries. 7 Almost one third of head injuries involved skull fractures and CT imaging demonstrated significant intracranial haemorrhage in one fifth of these head injury patients.…”
Section: Head Injurymentioning
confidence: 99%
See 1 more Smart Citation